Life cycle design of fully bio-based poly(lactic acid) composites with high flame retardancy, UV resistance, and degradation capacity. (1st August 2022) - Qiu, Shuang; Sun, Jun; Li, Yuchun; Zhu, Tao; Li, Hongfei; Gu, Xiaoyu; Fei, Bin; Zhang, Sheng
Abstract: Polylactic acid (PLA) is flammable, susceptible to UV light, and slow during degradation in nature, which limits the expansion of its application fields. Herein, a multifunctional bioderived additive (PA@TA-CS) was prepared by free radical grafting reaction between chitosan (CS) and tannic acid (TA) with the coating of phytic acid (PA) to achieve an all-round improvement of PLA. Only 3%PA@TA-CS in PLA increased the LOI value to 26.9%, upgraded the UL-94 level to V-0, and blocked nearly 99% UV light. In addition, by the presence of PA@TA-CS, the degree of molecular chain scission caused by hydrolysis and microbial degradation was significantly intensified. This work inherited the idea of returning to nature from nature and provided an effective strategy for extending the service life of bioplastics. Graphical abstract: Image 1 Highlights: A fully bio-based additive PA@TA-CS is designed and synthesized by an organic solvent-free method. Incorporation of PA@TA-CS imparts a desirable UL-94 V-0 rating to PLA at low loading. 3 wt%PA@TA-CS can endow PLA with excellent UV-resistance property. PA@TA-CS accelerate the degradation rate of PLA, with the whole composite decomposing harmlessly in the soil.